505 INTERLEUKIN-6, C-REACTIVE PROTEIN, FIBRINOGEN, AND RISK OF RECURRENCE AFTER ISCHEMIC STROKE: SYSTEMATIC REVIEW AND META-ANALYSIS. (14th June 2021) - McCabe, J J; O'Reilly, E; Coveney, S; Harbison, J; Collins, R; Healy, L; McManus, J; Mulcahy, R; Moynihan, B; Cassidy, T; Hsu, F; Worrall, B; et al.
Abstract: Background: Recent randomised trials showed benefit for anti-inflammatory therapies in coronary disease but excluded stroke. The prognostic value of blood inflammatory markers after stroke is uncertain and guidelines do not recommend their routine measurement for risk stratification. Methods: We performed a systematic review and meta-analysis of studies investigating the association of C-reactive protein (CRP), interleukin-6 (IL-6) and fibrinogen and risk of recurrent stroke or major vascular events (MVEs). We searched EMBASE and Ovid Medline until 10/1/19. Random-effects meta-analysis was performed for studies reporting comparable effect measures. Results: Of 2, 515 reports identified, 39 met eligibility criteria (IL-6, n = 10; CRP, n = 33; fibrinogen, n = 16). An association with recurrent stroke was reported in 12/26 studies (CRP), 2/11 (fibrinogen) and 3/6 (IL-6). On random-effects meta-analysis of comparable studies, CRP was associated with an increased risk of recurrent stroke [pooled hazard ratio (HR) per 1 standard-deviation (SD) increase in loge-CRP (1.14, 95% CI 1.06-1.22, p < 0.01)] and MVEs (pooled HR 1.21, CI 1.10-1.34, p < 0.01). Fibrinogen was also associated with recurrent stroke (HR 1.26, CI 1.07-1.47, p < 0.01) and MVEs (HR 1.31, 95% CI 1.15-1.49, p < 0.01). Trends were identified for IL-6 for recurrent stroke (HR per 1-SD increase 1.17, CI 0.97-1.41, p = 0.10) and MVEs (HR 1.22, CI 0.96-1.55, p = 0.10). Conclusion: Despite evidence suggesting an association between inflammatory markers and post-stroke vascular recurrence, substantial methodological heterogeneity was apparent between studies. Individual-patient pooled analysis and standardisation of methods are needed to determine the prognostic role of blood inflammatory markers and to improve patient selection for randomised trials of inflammatory therapies.